2017
DOI: 10.1111/nmo.13157
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid receptor 3 activation suppresses neurogenic motility in rat proximal colon

Abstract: Background: Short-chain fatty acids (SCFA) are microbial fermentation products ab-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
3
39
0
3
Order By: Relevance
“…Ffar3 expression has been demonstrated in cholinergic and nitrergic neurons of the myenteric plexus of the rat colon and in the myenteric plexus of the mouse small intestine . The inhibitory effect of SCFAs was observed in the presence of L‐NAME and MRS 2500, indicating that it is not mediated via the release of nitric oxide (NO) or purines acting on the P2Y 1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Ffar3 expression has been demonstrated in cholinergic and nitrergic neurons of the myenteric plexus of the rat colon and in the myenteric plexus of the mouse small intestine . The inhibitory effect of SCFAs was observed in the presence of L‐NAME and MRS 2500, indicating that it is not mediated via the release of nitric oxide (NO) or purines acting on the P2Y 1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this selective FFA2 agonist suppressed insulin levels in vivo, so we concluded that FFA2 could be a therapeutic target for obesity rather than type 2 diabetes . In contrast, FFA3 signaling appears to be primarily neural and in the GI tract may involve cholinergic nicotinic (in the rat ascending colon) and 5‐hydroxytryptamine (5‐HT) mechanisms and possibly vasoactive intestinal polypeptide (VIP), although FFA3 expression has also been observed in human colon epithelia . Species variations in the signaling bias of FFA2 and FFA3 agonists have presented significant challenges for their translation .…”
Section: Introductionmentioning
confidence: 91%
“…While little is known of the mechanisms of response to BCFA in the gut, the responses to SCFAs (mainly acetate, propionate, and butyrate) are mediated through the fatty acid receptor 2 (FFA2) and/or 3 (FFA3) formerly known as GPR43 and GPR41, respectively. These receptors are expressed in a variety of cells in the gut including enteroendocrine cells, adipocytes, pancreatic cells, immune cells, and enteric neurons; however, their expression in smooth muscle has not been studied [4,5,[7][8][9][10][30][31][32][33][34][35]. Similarly, their role in mediating the response to BCFA has not been studied in any of these cell types in any detail.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of SCFA on mucosal health and function has been studied more extensively than the effects on motility although several studies suggest that SCFA increase colonic motility and secretion via stimulation of neural and/or serotonin mediated pathways [29][30][31][32][33][34][35]. Direct contractile effects of SCFA on rat colonic smooth muscle have been reported, however, little is known of the effects of BCFA on colonic smooth muscle [36].…”
Section: Introductionmentioning
confidence: 99%